PROTEOLYTIC ENZYMES IN CHEESE MAKING - Aktayeva , S.; Akishev , ZH.; Khassenov , B. (Eurasian Journal of Applied Biotechnology, 2018)
There has been an increasing consumer demand for cheese along with a search for products with new organoleptic parameters, which has resulted in extensive research on alternative milk coagulants. The ratio of proteolytic activity to milk-clotting activity determines the requirements for proteases used in the cheese making process. To date, plant enzymes have largely been used for this purpose, along with traditional enzymes of animal origin, chymosin and pepsin. The most popular types of proteases used in the food industry, especially in cheese making, are plant proteases belonging to the cysteine (papain, bromelain, ficin), aspartate (cinarase, cardosin), and serine (kukumizin, leucine) group of proteases. The aspartate proteases of microbial origin mucorpepsin and endotyapepsin have found wide application in cheese production due to low production costs and high organoleptic characteristics of the final product. The use of plant and microbial milk-clotting enzymes as an alternative to animal-derived enzymes allows not only to diversify the assortment of cheeses on the market but also to solve ethical and economic issues. In addition, vegetable and microbial preparations meet the requirements of vegetarianism, halal, and kosher food, thus further opening the market.